Polite Racism: A Pragmatic Analysis of Racial Implicature in Get Out - Azhari, Rizky Maulana; Prihandini, Asih; Sari, Retno Purwani (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2025)
This study explores how language in the psychological thriller Get Out (2017), directed by Jordan Peele, conveys racism through polite yet indirect utterances. Although the white characters appear friendly, their language subtly reinforces racial stereotypes. Drawing on Grice’s theory of implicature (1975) and Searle’s speech act theory (1969), this research examines how pragmatic features reveal underlying racial bias. Using a descriptive qualitative method, the study analyzes 17 selected dialogues between the protagonist, Chris, and white characters during his visit to his girlfriend’s family. The findings show that implicatures conceal power imbalances and racial discomfort, while indirect speech acts mask prejudice beneath seemingly supportive comments. These results suggest that film serves not only to entertain but also to reflect and reinforces social issues like racism. Addressing a gap where pragmatic analysis is underused in film dialogue, this study demonstrates how everyday language can conceal power and bias in seemingly ordinary interactions. Keywords: Indirect Speech Acts, Conversational Implicature, Racial Bias, Language Use, Get Out